Five Co-ordinated Organo Magnesium(II) Complexes of Triazene-1-Oxides - Sharma, Ramdhar; Thakur, A.K.; Chaudhary, S.N.; Rai, S.B. (Asian Journal of Chemistry, 2010)
Five co-ordinate complexes of organomagnesium(II) have been reported. Grignard reagents in (1 : 1) and (1 : 2) molar ratio interact with alcoholic solution of variedly substituted monobasic triazene-1-oxides to give complexes of the type RMgT·2H2O and RMgT2. The former complexes react with dipyridyl/o-phenanthroline to give complexes of the type RMgT·dipy/o-phen. The monodentate ligands such as pyridine, 2-picoline, 4-picoline, aniline and N-alkylaniline etc. on reaction with RMgT·2H2O give complexes of the type RMgT·2L (L= monodentate ligands). In all the cases the co-ordination number of magnesium could be raised to a maximum of five. Failure to attain the usual six co-ordination for magnesium(II) appears to be due to the steric factors.